2012
DOI: 10.1039/c2dt11822j
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled 3D porous flowerlike α-Fe2O3 hierarchical nanostructures: Synthesis, growth mechanism, and their application in photocatalysis

Abstract: In this work, a facile route using a simple solvothermal reaction to synthesize 3D porous flowerlike hierarchical nanostructures (HNs) of α-Fe(2)O(3) without employing templates or matrices for self-assembly is presented. The morphology and compositional characteristics of the 3D HNs were investigated by various techniques. The 3D HNs composed of 2D nanopetals, were intercrossed with each other and constructed from nanobricks with a length of about 100 nm and a diameter of about 30 nm. Influencing factors such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(34 citation statements)
references
References 80 publications
2
32
0
Order By: Relevance
“…Second, it is reported that the efficiency of catalytic process depends on the adsorption and desorption of molecules on the surface of the catalyst. 18 of the catalyst can increase the photocatalytic reaction sites because of large relation area. As a result, the woodpile structure sample has a better degradation performance than that of the bulk material due to the fully developed inner space structure.…”
Section: Resultsmentioning
confidence: 99%
“…Second, it is reported that the efficiency of catalytic process depends on the adsorption and desorption of molecules on the surface of the catalyst. 18 of the catalyst can increase the photocatalytic reaction sites because of large relation area. As a result, the woodpile structure sample has a better degradation performance than that of the bulk material due to the fully developed inner space structure.…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al reported the synthesis of hematite (␣-Fe 2 O 3 ) nanocatalysts with welldefined architecture [28]. Zhu et al prepared 3D porous flowerlike hierarchical nanostructures of ␣-Fe 2 O 3 using an isopropyl alcoholmediated self-assembly solvothermal reaction [29]. In addition, Zhao et al succeeded in the fabrication of iron-modified rectorite bifunction material using ultrasonic-assisted ion-exchange and hydrolysis [30].…”
Section: Introductionmentioning
confidence: 98%
“…Figure 1 On the basis of previous studies [3,[14][15][16][17][18][19][20][21][22][23] and the above results, the possible growth processes of the ZnO HBDMs can be schematically illustrated, as shown in figure 3. First, numerous ZnAc 2 was hydrolyzed in the highly basic reaction solution, and Zn(OH) 4 2− ions were first formed. Then, under solvothermal conditions, a large number of tiny ZnO nanoparticles spontaneously appeared from the dehydration of Zn(OH) 4 2− ions by initial homogeneous nucleation.…”
Section: Methodsmentioning
confidence: 99%
“…First, numerous ZnAc 2 was hydrolyzed in the highly basic reaction solution, and Zn(OH) 4 2− ions were first formed. Then, under solvothermal conditions, a large number of tiny ZnO nanoparticles spontaneously appeared from the dehydration of Zn(OH) 4 2− ions by initial homogeneous nucleation. The freshly crystalline nanoparticles are unstable and have a tendency to aggregate together and developed into larger crystals, which may be driven by the minimization of interfacial energy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation